Making Simple Repairs: Door and Lock Problems - Mary N. Harrison (EDIS)
Getting stuck outside of your apartment or in a room can be frustrating. Prevent this from happening by following some simple rules and doing some minor repairs. This document is FCS5234-06 one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.